New Crepidium species (Orchidaceae, Malaxidinae) from the Island of Negros, Philippines - Margonska, Hanna B (Phytotaxa, 2014)
In 2013, when Mr Ravan Schneider with his wife Josephine came back from their photo tour on the Samar Island National Park (Philippines), they made a short stop in the small village of Marabut. At the food kiosk, Schneider came across in the garden next door some terrestrial orchids. Among others, there was a Crepidium plant with conspicuous leaf coloration. One of the plants had a fresh inflorescence, and he asked the owner if he could have this plant. The owner of the plants said that the plants came from about 10 kilometres from Marabut on a logging and mining road. Schneider was given the plant, which was luck because after typhoon Haynan (2013) not much remained of Marabut. In his garden the plants grew well. Upon blooming in November 2013, the plants and flowers were photographed, samples of the plant were dried and some flowers additionally were preserved in Copenhagen mixture for detailed study.